A caracterização de gramáticas paraenses no contexto de gramatização brasileira do português no Pará - MELO, Rosane Barros de (2022)
This work is a historical and linguistic study whose subject is The characterization of Pará grammars in the context of Brazilian grammatization of Portuguese in Pará. In the study, are analysed two compendiums: Primeira Grammatica da Infancia, by Vilhena Alves, and Gramática Primária da Língua Portuguesa, by Paulino de Brito. The two grammars were produced in the late nineteenth century in the state of Pará. The works were approved for use by the state’s primary schools. Thus, the general objective of the investigation is to understand the Brazilian grammatization process of Portuguese in Pará. To achieved objective, we established as the specific objectives, understand the grammatization process in Brazil, to understand the importance of authors of primary grammars from Pará for the history of education in the Amazon, and analyze the main physical and pedagogical characteristics of two Pará grammars of the late nineteenth century. The method used is bibliographic search and document search. The main theoreticians of the research are: Auroux (1992), Orlandi (2001), Fávero and Molina (2006), Fávero (2000), Colombat; Fournier; Puech (2017) and Moreira (1979). The Brazilian grammatization process of Portuguese in Pará is fruitful due to the large volume of grammars produced in the state in the late 19th and early 20th centuries. The analysis of the two grammars revealed that both Vilhena Alves and Paulino de Brito bring important contributions to the Brazilian grammatization process of Portuguese in Pará, because already present marks of the scientific current, especially Paulino de Brito, who critically analyzes facts of the language in the light of comparative grammar.